Preparation and Characterization of Glass-Ceramic Foam from Clay-Rich Waste Diatomaceous Earth - Sedlačík, Martin; Nguyen, Martin; Opravil, Tomáš; Sokolář, Radomír (Materials (Basel, Switzerland), 2022)
In this study, the potential use of waste diatomaceous earth from the production of diatomaceous earth for filtration purposes, as an alternative raw material for foam glass production, was explored. The chemical and mineralogical composition and the high temperature behavior of waste diatomite were studied to assess its suitability for foam glass production. Glass-ceramic foams were prepared using NaOH solution as a foaming agent, via a hydrate mechanism. The influence of different pretreatments and firing temperatures on the foam's structure, bulk density and compressive strength was investigated. High temperature behavior was studied using TG/DTA analysis and high temperature microscopy. Phase composition was studied using X-ray diffraction analysis. Glass-ceramic foam samples of a high porosity comparable to conventional foam glass products were fabricated. The pretreatment temperature, foaming temperature and sintering holding time were found to have a significant influence on foam properties. With increased pretreatment temperature, pyrogenic carbon from the thermal decomposition of organic matter contained in the raw material acted as an additional foaming agent and remained partially unoxidized in prepared foams. The bulk densities of prepared samples ranged from 150 kg/m3 to 510 kg/m3 and their compressive strengths were between 140 and 1270 kPa.
Keywords: waste diatomaceous earth; porous materials; secondary materials; nepheline; foam glass-ceramics